2023
DOI: 10.1007/s11071-023-08300-5
|View full text |Cite
|
Sign up to set email alerts
|

Model reduction for constrained mechanical systems via spectral submanifolds

Abstract: Dynamical systems are often subject to algebraic constraints in conjunction with their governing ordinary differential equations. In particular, multibody systems are commonly subject to configuration constraints that define kinematic compatibility between the motion of different bodies. A full-scale numerical simulation of such constrained problems is challenging, making reduced-order models (ROMs) of paramount importance. In this work, we show how to use spectral submanifolds (SSMs) to construct rigorous ROM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…Many high-dimensional chaotic dynamical systems can be approximated by a low-dimensional system (35)(36)(37)(38). Although the underlying dynamics of earthquakes and Slow Slip cycles are often chaotic (24)(25)(26)(27)(28), in certain examples, it has been observed that the chaotic attractors are low dimensional (8,39) which mathematically implies that we can approximate the evolution of the sequence of events using parameters in a finite-dimensional space instead of an infinite function space.…”
Section: Model Reduction and Forecast Schemementioning
confidence: 99%
“…Many high-dimensional chaotic dynamical systems can be approximated by a low-dimensional system (35)(36)(37)(38). Although the underlying dynamics of earthquakes and Slow Slip cycles are often chaotic (24)(25)(26)(27)(28), in certain examples, it has been observed that the chaotic attractors are low dimensional (8,39) which mathematically implies that we can approximate the evolution of the sequence of events using parameters in a finite-dimensional space instead of an infinite function space.…”
Section: Model Reduction and Forecast Schemementioning
confidence: 99%
“…In its initial formulation, SSM reduction constructed the parametrization of the invariant manifold and the reduced dynamics as a Taylor expansion around a steady state, which proved fruitful in reduced-order modelling for general mechanical systems (e.g. Jain & Haller 2022; Li, Jain & Haller 2023). In addition to its strict mathematical foundation, a noteworthy advantage of SSM-based model reduction over projection-based methods is that the dimension of the slowest non-resonant spectral subspace a priori determines the dimension of the reduced-order model.…”
Section: Introductionmentioning
confidence: 99%
“…DAEs are for example the starting formalism of the Manlab numerical continuation package that uses the asymptotic numerical method on quadratic DAE to compute their solutions as a parameter is varied [43], or can be used for time integration [44]. Considering the computation of reduced-order models for DAE using invariant manifolds has been considered recently in [45] with the spectral submanifold framework. However, in this work the authors transform the DAE into an ODE by taking the derivative of the algebraic equation with relation to time as many times as necessary.…”
Section: Introductionmentioning
confidence: 99%
“…45) Taylor (order 11) NF (order 45) Taylor (order 21) NF (order 45) Taylor (order 31) NF (order 45) ODE for sin NF (order 45) ODE for sin NF (order 45) Chebyshev 1 (cartesian)) NF (order 45) Chebyshev 2 (quaternion-like)) NF (order 45) Chebyshev 3 NF (order 45) Chebyshev 4…”
unclassified